التراكيـب المجازية و إمكانـات التأويـل قراءة في إبداع الدلالات الجديدة ديوان السفر الشاق لنور الدين درويش - طبني, صفية (Sciences humaines; Vol. 22 (2011): SCIENCES HUMAINES)
تسمح هذه الدراسة برصد بعض النماذج و التراكيب الانزياحية التي تفترض نسقا من القواعد, تلك التي تجعل المتكلم يتمتع بطاقة ابداعية تتكيء على قواعد و مباديء تمثل معطيات لهذا المتكلم مما يجعلها تميزه عن غيره من المتكلمين و المبدعين في الآن نفسه , فيصبح المتلقي مبدعا من خلال رصد تلك الانزياحات المختلفة وإعطاء ذلك العمل قيمته الحقيقية     This study allows some of the allegorical samples and components which demand some grammatical cohesion which allow the speaker to have innovative energy relying on rules and principles exemplifying competence for him which makes that speaker distinct from other speakers and innovators at the same time, so the receiver becomes an innovator by detecting those allegories and giving it its real value.